COGNITIVE POTENTIAL AND ITS PREDICTORS IN CHILDREN FROM A RURAL DISTRICT OF PAKISTAN - Gilani, Irum (Journal of Ayub Medical College Abbottabad, 2017)
Background: Effective interventions are available to reduce cognitive deficit currently estimated to affect more than 200 million children under 5 years of age in developing countries. However, developing world's investment is negligible in this regard mainly because of non-existent global indicators to monitor progress with respect to the childhood cognitive development. Intelligence Quotient (IQ) or Full Scale Intelligence Quotient (FSIQ) is an indicator of the cognitive development. This study was designed to assess cognitive potential of 6-7 years old children from a rural district of Pakistan by calculating their FSIQ. Predictors of the FSIQ were also determined. Method: This cross-sectional research was carried out in 40 rural Union Councils (UCs) of 2 sub-districts in district Rawalpindi utilizing simple random sampling technique. Wechsler Pre-school and Primary Scale of Intelligence (WPPSI-IV) was administered to 6-7 years old children (n=300) for measuring their FSIQ. Results: FSIQ of rural Pakistani children, relative to the normative sample, was found to be in the category of low-average. Findings of multiple regression analysis concluded grade/class of the child as the most influential predictor of the FSIQ followed by the level of mother's and then father's education. Conclusion: FSIQ of the rural Pakistani children, relative to the normative sample, was found to be in the category of low-average. Predictors of the FSIQ, seen in this research, were school grades and non-educated parents of the children warranting future research on the contribution of environmental influences to the variability in cognitive potential. Keywords:Cognitive; Rural; FSIQ; Children; Predictor; Pakistan; Indicator